WAITING LINE THEORY AS A TOOL FOR DECISION MAKING IN SMEs (STUDY : SMEs MOTORCYCLE WASH SEMARANG) - Nuryanto, Imam (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
This study was conducted to determine the performance of SMEs. SMEs need to have a sustainable competitive advantage one way that can be achieved is making the right decision in the field of operations. Â Samples were taken using purposive sampling of 30 SMEs, the type of data used is primary data with questionnaire data collection methods. Analysis techniques in measuring performance waiting line using analysis tool POM for windows, which is software that helps decision-making in the field of operations management. Â The analysis showed that the performance of 47% of SMEs have been efficient, but 53% of SMEs have not been efficient. This is caused by several factors: the length of service providers are still ignoring the queue (waiting line), service providers do not add facilities (service facilities) and service level (Î¼) is lower than the arrival rate (Î»). So that the necessary decisions in the waiting line system, with appropriate decision-making SMEs can enhance the sustainable competitive advantage. Â